2011
DOI: 10.1007/s11205-011-9843-4
|View full text |Cite
|
Sign up to set email alerts
|

Validity and the Consequences of Test Interpretation and Use

Abstract: Consequential validity, Early development instrument, Educational achievement, Psychological assessment, Testing, Multilevel measures, Social consequences, Test interpretation, Validity, Value implications, Values,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
108
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 21 publications
1
108
0
1
Order By: Relevance
“…Therefore, we decided that all chapters would, at least, follow the generic framework in the Standards (AERA et al 1999) wherein five sources of validity evidence were of focus: (a) content-related, (b) response processes, (c) internal structure, (d) associations with other variables, and (e) consequences. The syntheses also addressed whether recent work in validity theory was cited as informing the validation practice (e.g., Hubley and Zumbo 1996, 2011, 2013Kane 2006;Messick 1989;Zumbo 2007Zumbo , 2009.…”
Section: Prefacementioning
confidence: 99%
“…Therefore, we decided that all chapters would, at least, follow the generic framework in the Standards (AERA et al 1999) wherein five sources of validity evidence were of focus: (a) content-related, (b) response processes, (c) internal structure, (d) associations with other variables, and (e) consequences. The syntheses also addressed whether recent work in validity theory was cited as informing the validation practice (e.g., Hubley and Zumbo 1996, 2011, 2013Kane 2006;Messick 1989;Zumbo 2007Zumbo , 2009.…”
Section: Prefacementioning
confidence: 99%
“…220-221). Based on this description, we expect the degree of validity of a measure to vary by context and/or respondents characteristics [37,38]. The above evidence suggested that both versions of the CWEQ II are less valid and reliable measures when used with nurses who have high levels of SE than when used with nurses who have lower levels of SE (but not the lowest).…”
Section: Validity and Reliabilitymentioning
confidence: 97%
“…Second, unlike traditional views of validity that have described validity as a property of the measure itself, more contemporary views have described it as the extent to which empirical evidence supports the intended meaning of test scores for its proposed purpose [37,38]. In other words, measurement scholars acknowledge "validity is about whether the inference one makes is appropriate, meaningful, and useful given the individual or sample with which one is dealing, and the context in which the test user and individual/sample are working [38] (pp. 220-221).…”
Section: Validity and Reliabilitymentioning
confidence: 99%
“…Hubley and Zumbo (2011) introduced a new conceptualization of test validity that draws a clearer attention to the inherent elements (i.e., values), external influences (i.e., social consequences and side effects), and the process of validation in validity. The framework is meant to highlight the test's purpose and use, and its concomitant values, social and personal consequences, as well as social and personal side effects.…”
Section: How Standards Are Tied To Validity Theory and A Focus On Tesmentioning
confidence: 99%
“…Very importantly, these consequences and/or side effects (either personal and/or social) may also influence test score inferences and use. Second, test-score inference and use is effected Hubley and Zumbo (2011) with permission of Social Indic. Res, Vol.…”
Section: How Standards Are Tied To Validity Theory and A Focus On Tesmentioning
confidence: 99%